Recent progress in optoelectronic memristors for neuromorphic and in-memory computation - Pereira, Maria Elias (2023)
Funding Information: This work is funded by FEDER funds through the COMPETE 2020 Programme and National Funds through the FCT—Portuguese Foundation for Science and Technology, under the scope of the projects UIDB/50025/2020-2023, LA/P/0037/2020, doctoral Grant DFA/BD/8335/2020. TERRAMETA project has also funded this work and received funding from the Smart Networks and Services Joint Undertaking (SNS JU) under the European Union’s Horizon Europe research and innovation programme under Grant Agreement No 101097101. Publisher Copyright: © 2023 The Author(s). Published by IOP Publishing Ltd.